The Human Resources for Health Crisis in Zambia : An Outcome of Health Worker Entry, Exit, and Performance within the National Health Labor Market - Herbst, Christopher H.; Vledder, Monique; Campbell, Karen; Sjöblom, Mirja; Soucat, Agnes (World Bank, 2012)
This report compiles recent evidence on the Zambian health labor market and provides some baseline information on human resources for health (HRH) to help the government address its HRH challenges. Rather than focusing on making policy recommendations, the report is designed to be a source book to benefit and fuel discussions related to HRH in Zambia. Most of the data presented in the report covers the period 2005-08. The report analyzes the national health labor market to better understand the available evidence related to the stock, distribution, and performance of HRH in Zambia (that is, the HRH outcomes). It aims to explain those HRH outcomes by mapping, assessing, and analyzing pre-service education and labor market dynamics, that is, the flow of health workers into, within, and out of the health labor market, as well as the core factors influencing these dynamics. Finally, this report examines the issue of access and equity of HRH. It finds that even if health workers are available, in either urban or rural areas, and performing adequately, the wealthy in Zambia have better access to services than the poor. This situation is found in most if not all other countries. The report finds that as far as access to health workers is concerned, the poor generally loose out. It also reveals that even if health workers are available, wealthier segments of the population often continue to have better access to health workers than poorer segments. Wealthier women have the highest probability of receiving any antenatal care. There is an even steeper pro-rich gradient in delivery attendance in Zambia. In contrast to antenatal care, there is little variation across socioeconomic quintiles among those seeking medical treatment for children with diarrhea or cough and fever. The poor are slightly more likely to be visited by a health worker and receive certain services during visits. The factors linked to these variations in use of services remain to be examined (they could be linked to expense, fear of receiving care from an individual belonging to a higher social stratum, or different gender, and so forth). Either way, they should be taken into consideration when planning to improve access for the poor to health care services and providers.